Does home equipment contribute to socioeconomic gradients in Australian children's physical activity, sedentary time and screen time? - Dot Dumuid; Timothy S. Olds; Lucy K. Lewis; Carol Maher (BMC, 2016)
Abstract Background Activity behaviours (physical activity, sedentary time and screen time) have been linked to health outcomes in childhood. Furthermore, socioeconomic disparities have been observed in both children's activity behaviours and health outcomes. Children's physical home environments may play a role in these relationships. This study aimed to examine the associations and interactions between children's physical home environment, socioeconomic status and moderate-to-vigorous physical activity, sedentary time and screen time. Methods Australian children (n = 528) aged 9-11 years from randomly selected schools participated in the cross-sectional International Study of Childhood Obesity, Lifestyle and the Environment. Children's physical home environment (access to equipment), socioeconomic status (household income and parental education) and demographic variables (gender and family structure) were determined by parental questionnaire. Moderate-to-vigorous physical activity and sedentary time were measured objectively by 7-day 24-h accelerometry. Screen time was obtained from child survey. The associations between the physical home environment, socioeconomic status and moderate-to-vigorous physical activity, sedentary time and screen time were examined for 427 children, using analysis of covariance, and linear and logistic regression, with adjustment for gender and family structure. Results The presence of TVs (p < 0.01) and video game consoles (p < 0.01) in children's bedrooms, and child possession of handheld video games (p = 0.04), cell phones (p < 0.01) and music devices (p = 0.04) was significantly and positively associated with screen time. Ownership of these devices (with the exception of music devices) was inversely related to socioeconomic status (parental education). Children's moderate-to-vigorous intensity physical activity (p = 0.04) and possession of active play equipment (p = 0.04) were both positively associated with socioeconomic status (household income), but were not related to each other (with the exception of bicycle ownership). Conclusions Children with less electronic devices, particularly in their bedrooms, participated in less screen time, regardless of socioeconomic status. Socioeconomic disparities were identified in children's moderate-to-vigorous physical activity, however socioeconomic status was inconsistently related to possession of active play equipment. Home active play equipment was therefore not a clear contributor to the socioeconomic gradients in Australian children's moderate-to-vigorous physical activity.